2021
DOI: 10.1111/hsc.13512
|View full text |Cite
|
Sign up to set email alerts
|

Supported decision‐making and mental capacity assessment in care homes: A qualitative study

Abstract: Up to 75% of UK care home residents may lack the mental capacity to make certain decisions (Wade, Clinical Rehabilitation, 2019, 33, 1561-1570. Care home staff need evidence-based tools to help them assess residents' mental capacity and provide decision-making support (NICE, Decision-making and mental capacity NICE guideline NG108, 2018). The Mental Capacity Assessment Support Toolkit (MCAST) was designed to support multidisciplinary healthcare staff to prepare, complete and document legally compliant mental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…Finally, participants in our study reported longer‐standing issues surrounding the effective implementation of the MCA. Our findings reaffirm previously reported issues regarding the complexity and bureaucratic burden of MCA safeguarding processes (Carpenter et al., 2014 ) and inconsistent and variable knowledge of the MCA (Barry et al., 2020 ; Bartlett, 2014 ; House of Lords, 2014 ; Jayes et al., 2021 ; Lennard, 2015 ; Manthorpe & Samsi, 2016 ). The upcoming transition from the DoLS system to the new Liberty Protection Safeguards (LPS) presents a unique opportunity to ensure that the relevant provisions of law are well understood by the professionals who will play a leading role in implementing them.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, participants in our study reported longer‐standing issues surrounding the effective implementation of the MCA. Our findings reaffirm previously reported issues regarding the complexity and bureaucratic burden of MCA safeguarding processes (Carpenter et al., 2014 ) and inconsistent and variable knowledge of the MCA (Barry et al., 2020 ; Bartlett, 2014 ; House of Lords, 2014 ; Jayes et al., 2021 ; Lennard, 2015 ; Manthorpe & Samsi, 2016 ). The upcoming transition from the DoLS system to the new Liberty Protection Safeguards (LPS) presents a unique opportunity to ensure that the relevant provisions of law are well understood by the professionals who will play a leading role in implementing them.…”
Section: Discussionsupporting
confidence: 91%
“…Legfőbb kihívásként az időmenedzsmentet, az adminisztrációt és a folyamatban részt vevő további szereplőkkel való együttműködést említik. Az interjúalanyok egyetértenek abban, hogy az MCAST eszköztár hatékonyan támogathatná munkájukat a jövőben (Jayes et al, 2022).…”
Section: Aktuális Helyzetképunclassified
“…Research and scholarship document that people with disabilities can use (and have used) SDM to make everyday life decisions (Browning et al, 2021;Harding & Taşcıoğlu, 2018), engage in social and romantic relationships (Boni-Saenz, 2015), and take part in and consent to health care (Browning et al, 2014;Enck, 2021;Kokanović et al, 2018;Sapolsky, 2017), legal representation (Gooding, et al, 2023), and medical and mental health assessments (Jayes, Austin, & Brown, 2022;Jayes, Palmer, & Enderby, 2022). Thus, empowering people to use SDM-including people with extremely limited cognitive capacity (Peterson et al, 2022)-is "compatible with, and may even promote, their overall well-being.…”
Section: Sdm As An Alternative To Guardianship and A Way To Enhance S...mentioning
confidence: 99%